Indonesia rising the repositioning of Asia's third giant - Reid, Anthony 1939- (Indonesia update series, 2012)
There are reasons for thinking that this is at last Indonesia's moment on the world stage. Having successfully negotiated its difficult transition to democracy after 1998, Indonesia has held three popular elections with a low level of violence by the standards of southern Asia. Recently its economic growth rate has been high (above 6 per cent a year) and rising, where China's has been dropping and the developed world has been in crisis. Indonesia's admission in 2009 to the G20 club of the world's most influential states seemed to confirm a status implied by its size, as the world's fourth-largest country by population, and the largest with a Muslim majority. Some international pundits have been declaring that Indonesia is the new star to watch, and that its long-awaited moment in the sun may at last have arrived.